Effect of initial temperature on electrochemical and thermal characteristics of a lithium-ion battery during charging process. (August 2020) - Tan, Meixian; Gan, Yunhua; Liang, Jialin; He, Linfeng; Li, Yong; Song, Shuran; Shi, Yanling
Highlights: Effect of initial temperature of a lithium battery during charging is studied. Distributions of local current density and heat generation rate are analyzed. Non-uniformity of local current density increases at lower initial temperature. Charging energy efficiency varies at different initial temperatures and C-rates. Abstract: Due to the discharging or long-term placing, the initial temperature of a lithium-ion battery during charging is different, which may lead to various electrochemical and thermal characteristics. An electrochemical-thermal coupled model is developed for a lithium-ion battery and experimentally validated. The local current density, heat generation rate and charging energy efficiency of the battery during charging at different initial temperatures are numerically investigated. The spatial distribution of local current density of the battery cell is non-uniform at different initial temperatures. And the non-uniformity increases with the decreasing of initial temperature, especially in the negative electrode. Initial temperature influences the spatial and temporal distributions of heat generation rate in the battery cell. Most of the heat (over 95%) is generated in the electrodes. And the part of irreversible heat contributes to over 60% of the total heat generation in the negative electrode. The charging energy efficiency changes with the difference of the total irreversible heat and the input charging energy. The charging energy efficiency of the battery increases with the increasing of initial temperature at 0.5 C charging rate, while it will decrease after the initial temperature exceeds 40 °C and 25 °C at 1 C and 2 C charging rate, respectively. So it should use reasonable charging rates at different initial temperatures. These findings give help for the battery management systems design to achieve higher charging energy efficiency.